Enhancing Learning Motivation Of PrimarySchool Students Through Digital Games - Ganiyeva Gulkhayyo Islom qizi (Euro Asian Journal Publishing, 2025)
This article examines the role of digital games in increasing learning motivation among primary school students. It explores the psychological and pedagogical foundations of game-based learning, as well as effective methods of integrating digital games into the educational process. The educational, developmental, and motivational functions of digital games are analyzed, and methodological recommendations aimed at supporting active learning needs in young learners are provided.
Keywords: Digital Games; Learning Motivation; Primary Education